PERBEDAAN KUALITAS CITRA MRI LUMBAL SEKUEN T2 TSE FAT SATURATION WEAK DAN STRONG PADA KASUS HNP - Lutfatul Fitriana; Alan Samudra; Hernastiti Sedya Utami; Fani Gimnastiar; Dea Zalfa Cahyla Adi; Muhamad Andin Dwi Pranata (Universitas Muhammadiyah Klaten, 2025)
Fat Saturation has two modes, namely Weak Mode and Strong Mode, thus further research is needed to determine whether there is a difference in image quality between the two. This study aims to identify the difference in image quality between T2 TSE Fat Saturation Weak Mode and Strong Mode in lumbar MRI for cases of Herniated Nucleus Pulposus (HNP). Data collection was conducted from October to November 2024 at the Radiology Department of SMC Telogorejo Hospital using a Siemens 1.5T MRI scanner. A total of ten patient images were analyzed by calculating the Signal to Noise Ratio (SNR) values in the anatomical structures of the Bone Marrow, Intervertebral Disc, CSF, and Spinal Cord using Radian DICOM Viewer. Statistical analysis was performed using SPSS. The Wilcoxon test showed a significant difference only in the Bone Marrow anatomy (p < 0.05). No significant differences were found in the Intervertebral Disc, CSF, or Spinal Cord (p > 0.05). The Weak Mode also provided a faster scanning time, making it more recommended for lumbar MRI examinations in HNP cases, especially since its image quality is nearly equivalent to Strong Mode for most anatomical structures. This study indicates that there was no significant difference in the Intervertebral Disc anatomy, which is the primary location of HNP. Therefore, Weak Mode is more recommended as it offers greater patient comfort through shorter examination time.